A hydrolytically stable anionic layered indium–organic framework for the efficient removal of 90Sr from seawater. Issue 48 (28th November 2019) - Li, Guodong; Ji, Guoxun; Liu, Wei; Zhang, Jiarong; Song, Liping; Cheng, Liwei; Wang, Xia; Wang, Yanlong; Liu, Jianjun; Chen, Xudan; Sun, Xinli; Diwu, Juan
Abstract : A layered compound with superior selectivity and removal ability toward 90 Sr over a wide pH range. Abstract : Efficient removal of radioactive 90 Sr from nuclear waste solutions and natural water systems is of vital importance due to its radioactive nature and high mobility. We present here an anionic layered compound (NC4 H12 )(NC2 H8 )2 [In3 (pydc)6 ]·13.1H2 O (SZ-6 ; pydc = 2, 5-pyridinedicarboxylic acid) with the potential remediation ability towards radioactive Sr 2+ from seawater. This material exhibits excellent β and γ radiation resistance both in air and in aqueous solutions. Besides, this material could maintain its structural integrity in real seawater for 77 days. The adsorption experiment results show that SZ-6 exhibits superior Sr 2+ removal capability over a wide pH range from 4 to 12 with fast adsorption kinetics and high selectivity. The effective removal of 90 Sr from real seawater was demonstrated as well. Our results strongly suggest the potential application of SZ-6 for selectively capturing radionuclides in natural water systems.